An infant with poor weight gain and hypochloremic metabolic alkalosis: a case report - Alhammadi AH; Khalifa M; Alnaimi L (International Journal of General Medicine, 2014)
Ahmed H Alhammadi, Mohamed Khalifa, Lolwa Alnaimi Department of Pediatrics, Division of General Pediatrics, Hamad Medical Corporation, Doha, Qatar Abstract: Bartter syndrome is an autosomal recessive disease manifested by a defect in chloride transport in the thick loop of Henle, with different genetic origins and molecular pathophysiology. Children with Bartter syndrome generally present in early infancy with persistent polyuria and associated dehydration, electrolyte imbalance, and failure to thrive. Although early diagnosis and appropriate treatment of Bartter syndrome may improve the outcome, some children will progress to renal failure. We report a case of an 8-week-old infant who was admitted for electrolyte imbalance and failure to thrive. Laboratory studies revealed hypochloremic metabolic alkalosis with severe hypokalemia. Health care providers should consider Bartter syndrome when excessive chloride losses appear to be renal in origin and the patient has normal blood pressure and high levels of serum renin and aldosterone. Treatments, including indomethacin, spironolactone, and aggressive fluid and electrolyte replacement, may prevent renal failure in children with Bartter syndrome. Molecular genetics studies are indicated to identify the primary genetic defect. Keywords: Bartter syndrome, failure to thrive, metabolic alkalosis